Book reviews: “Teodor Bulboac˘a, Santosh B. Joshi, and Pranay Goswami, Complex Analysis: Theory and Applications”, de Gruyter, 2019, xii + 409 pages, ISBN 978-3-11-065782-1, e-ISBN (PDF) 978-3-11-065786-9, e-ISBN (EPUB) 978-3-11-065803-3 - KOHR, Gabriela (Studia Universitatis Babeș-Bolyai Mathematica, 2020)
The present book provides a modern presentation of various classical topics in complex analysis. As it is mentioned in the preface, the level of difficulty of the material increases gradually from chapter to chapter.